School Administrator and Teachers' Perceptions of Organizational Silence - Kahveci, Gokhan; Demirtas, Zulfu (Turkish Education Assoc, 2013)
The aim of this study is to inquire about the perception of administrators and teachers on organizational silence. The study followed a survey model. Data were collected from primary schools in Elazig in 2009-2010 education year. The sample of this research consists of 444 administrators and teachers in 20 primary schools that were chosen randomly. The results of the study show that the perception of women on organizational silence is higher and the participants of different branches such as Turkish and English are more silent than the others. The participants that have been working at schools for at least 6 years have higher perception. The age and teaching years of the participants show that their perceptions on organizational silence are nearly at the same level.
Okul yöneticisi ve ö?retmenlerin örgütsel sessizlik algilari
Keywords: Silence; primary school; organizational silence; employee